2016
DOI: 10.15376/biores.11.3.6407-6415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coating with Calcite together with Various Fire Retardants on the Fire Properties of Particleboard

Abstract: The fire properties of particleboard coated with calcite and a variety of fireretardants (FR) was investigated. Four different chemicals, boric acid (BA), borax (BX), dolomite (DOL), and melamine (MEL), were added at the concentration of 1.0%, 3.0%, and 5.0% by oven-dry weight of calcite. The particleboard panels were tested according to the ASTM-E 69 standard to investigate their fire-retardant properties. The determination of weight loss, temperature, and the release of O2, CO, and NO by the samples was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…They investigated the modulus of rupture (MOR), modulus of elasticity (MOE), limiting oxygen index (LOI), and simultaneous thermal analysis (TG-DSC) of MDF boards. Özdemir and Tutus (2016) investigated the effects of coating with calcite together with various fire retardants on the fire properties of particleboard. Taghiyari et al (2016) produced MDF from wollastonite fibers, camel-thorn, and wood fibers.…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the modulus of rupture (MOR), modulus of elasticity (MOE), limiting oxygen index (LOI), and simultaneous thermal analysis (TG-DSC) of MDF boards. Özdemir and Tutus (2016) investigated the effects of coating with calcite together with various fire retardants on the fire properties of particleboard. Taghiyari et al (2016) produced MDF from wollastonite fibers, camel-thorn, and wood fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Mahmood et al [16] stated that the thermal stability of the particleboard improved after various pre-treatment that could be attributed to the removal of noncellulosic impurities during regeneration of particles after pretreatment. Ozdemir and Tutus [17] also reported that particle materials are pre-treated to decrease the flammability with fire retardant chemicals. To date, only a few studies have carried out using NaCl salt as pre-treatment agent [15].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, non-flammable mineral fillers were used in composites, resulting in reduced heat release and weight [18]. Calcium carbonate (CaCO 3 ) is a carbonated mineral with the most stable polymorph [17]. Calcium carbonate is most widely used due to its features such as extensive sources, low cost, and non-toxic.…”
Section: Introductionmentioning
confidence: 99%
“…For fire protected chip‐ and particleboards or wood fibreboard compounds containing nitrogen, phosphorus, boron, zinc, calcium, magnesium, and combinations thereof are used as flame retardants . The use of bromine‐containing flame retardants for wood‐based panels has been studied poorly until now.…”
Section: Introductionmentioning
confidence: 99%